Increasing coastal slump activity impacts the release of sediment and organic carbon into the Arctic Ocean - Ramage, Justine Lucille; Irrgang, Anna Maria; Morgenstern, Anne; Lantuit, Hugues (Prof. Dr.) (Biogeosciences, 2018)
Retrogressive thaw slumps (RTSs) are among the most active thermokarst landforms in the Arctic and deliver a large amount of material to the Arctic Ocean. However, their contribution to the organic carbon (OC) budget is unknown. We provide the first estimate of the contribution of RTSs to the nearshore OC budget of the Yukon Coast, Canada, and describe the evolution of coastal RTSs between 1952 and 2011 in this area. We (1) describe the evolution of RTSs between 1952 and 2011; (2) calculate the volume of eroded material and stocks of OC mobilized through slumping, including soil organic carbon (SOC) and dissolved organic carbon (DOC); and (3) estimate the OC fluxes mobilized through slumping between 1972 and 2011. We identified RTSs using high- resolution satellite imagery from 2011 and geocoded aerial photographs from 1952 and 1972. To estimate the volume of eroded material, we applied spline interpolation on an airborne lidar dataset acquired in July 2013. We inferred the stocks of mobilized SOC and DOC from existing related literature. Our results show a 73% increase in the number of RTSs and 14% areal expansion between 1952 and 2011. In the study area, RTSs displaced at least 16.6 x 10(6) m(3) of material, 53% of which was ice, and mobilized 145.9 x 10(6) kg of OC. Between 1972 and 2011, 49 RTSs displaced 8.6 x 10(3) m(3) yr(-1) of material, adding 0.6% to the OC flux released by coastal retreat along the Yukon Coast. Our results show that the contribution of RTSs to the nearshore OC budget is non-negligible and should be included when estimating the quantity of OC released from the Arctic coast to the ocean.